Development of a novel RNA-based fibroblast growth factor receptor response signature (FGFR-PRS) for use in patients with urothelial cancer (UC). - Kirk L. Pappan; Gregory Mayhew; James M. Davison; Yoichiro Shibata; Joel Robert Eisner; Kirk Beebe; Michael Vance Milburn (Journal of Clinical Oncology, 2024)
548 Background: Interest in FGFR-targeted (FGFRi) therapies for UC or pan-tumor use is growing (ongoing clinical studies include erdafitinib (NCT05316155; NCT04172675; NCT03390504; NCT04083976), LOXO-435 (NCT05614739), and pemigatinib (NCT03914794) following accelerated approval of erdafitinib in locally advanced/metastatic (m) post-chemotherapy UC patients with FGFR2/3 (i.e., DNA mutations and fusions) alterations (ALT). However, ALT status may not fully capture all who may show clinical benefit as responses are observed in both ALT (+) and (-) patients. Improved test strategies are needed to identify patients most likely to respond to FGFRi. FGFR-PRS is an RNA-based signature developed to capture the biology of FGFR-active tumors independent ALT status and is intended to be used as a diagnostic (Dx) to identify a broader patient population likely to respond to FGFRi. Methods: Known oncogenic FGFR3 ALTs (S249C, R248C, FGFR3c-Y373C, FGFR3c-G370C, FGFR3:TACC3 and FGFR3:BAIAP2L1) were used as training labels for nearest centroid classifier development as described in Dabney et al, 2005 ( https://doi.org/10.1093/bioinformatics/bti681 ) using 2/3 of data from the TCGA BLCA dataset, predominantly comprised of muscle-invasive bladder cancer patients and a few mUC patients, for training. The resulting 80-gene signature was applied to the remaining 1/3 of TCGA and a separate BACI mUC dataset (Rose et al, 2021; https://doi.org/10.1038/s41416-021-01488-6) as test sets. In vitro drug sensitivity was evaluated using data from the Genomics of Drug Sensitivity in Cancer database (GDSC; https://www.cancerrxgene.org/ ). Differential gene expression (DGE) results were analyzed using WebGestalt 2019 (https://www.webgestalt.org/). Results: Thirteen and 18% of the TCGA and BACI UC cohorts were ALT (+), whereas 49% and 48% were FGFR-PRS (+) independent of ALT status. About half of the patients in either cohort were ALT (-)/ FGFR-PRS (-) and only 1% were ALT (+)/FGFR-PRS (-). FGFR 1-3 selective drugs had strong inverse correlations between FGFR-PRS score and IC50 across 18 GDSC bladder cancer cell lines. FGFR-PRS (+) samples had enhanced co-expression of FGFR3, FOXA1, and SHH and selected multiple differentiation ontologies. Conclusions: FGFR-PRS (+) captured most ALT (+) tumors and an additional 2X more with similar FGFR pathway activation. FGFR-PRS (+) tumors were associated with gene enrichments for ontologies linked to FGFR3 signaling. The correlation of FGFR-PRS score with in vitro FGFRi activity provided initial utility of the signature, which is undergoing clinical evaluation in the ALAMANCE retrospective study of UC patients treated with FGFRi or other standard-of-care therapies. Analytical validation is ongoing to support FGFR-PRS for use as a clinical trial assay and eventual Dx.